Spin wave damping in periodic and quasiperiodic magnonic structures. (29th March 2016) - Rychły, J; Kłos, J W; Krawczyk, M
Abstract: We investigated the lifetime of spin wave (SW) eigenmodes in periodic and quasiperiodic sequences of Py and Co wires. These materials differ significantly in damping coefficients, therefore, the spatial distribution of the mode's amplitude within the structure is important for the lifetime of collective SW excitations. Modes of the lower frequencies prefer to concentrate in Py wires, because of the lower ferromagnetic resonance (FMR) frequency for this material. This inhomogeneous distribution of amplitude of modes (with lower amplitude in material of higher damping and with higher amplitude in material of lower damping) is preferable for extending the lifetime of the collective excitations beyond the volume average of lifetimes for solid materials. We established the relation between the profile of the mode and its lifetime for periodic and quasiperiodic structures. We also performed comparative studies in order to find the differences resulting from complexity of the structure and enhancement of localization in the quasiperiodic system on the lifetime of SWs.